Liquid‐Like SiO2‐g‐PDMS Coatings on Wood Surfaces with Underwater Durability, Antifouling, Antismudge, and Self‐Healing Properties. (1st October 2018) - Wang, Yaru; Yan, Wenqing; Frey, Marion; Vidiella del Blanco, Marta; Schubert, Mark; Adobes‐Vidal, Maria; Cabane, Etienne
Abstract: Recent research on surfaces with special wettability has lead to the development of "liquid surfaces", obtained through the immobilization of a lubricant liquid on a porous interface, or through the grafting of flexible polymer chains on smooth surfaces. The latter method to fabricate durable protective coatings on wood surfaces is adapted in the current work. The method is based on a first modification with a silicon oxide layer, followed by the grafting of polydimethylsiloxane (PDMS) chains. The obtained surfaces are hydrophobic, and are highly durable when compared to classical superhydrophobic coatings, in particular after prolonged immersion in water. A self‐healing ability, provided by the rearrangement of the PDMS chains after plasma treatment, is reported herein. Finally, the coatings have antismudge, antifouling, and antibacterial properties. With durable water repelling properties, quick self‐healing ability, antismudge, antifouling, and antibacterial properties, the durability of wood is increased. This research demonstrates the protection potential of liquid‐like polymer coatings on wood, a material that will play an essential role in the transition toward more sustainable societies. Abstract : Wood is highly sustainable, but suffers from various drawbacks related to wettability questions. Here, a method to protect wood veneers against water sorption is shown. Through the deposition of a silica layer followed by the grafting of polydimethylsiloxane chains, a durable wood surface treatment, with some interesting properties, including antifouling, antismudging, reduced bacterial growth, and self‐healing, is developed.